Coagulation factor XII genetic variation, ex vivo thrombin generation, and stroke risk in the elderly: results from the Cardiovascular Health Study. (14th September 2015) - Olson, N. C.; Butenas, S.; Lange, L. A.; Lange, E. M.; Cushman, M.; Jenny, N. S.; Walston, J.; Souto, J. C.; Soria, J. M.; Chauhan, G.; Debette, S.; Longstreth, W. T.; et al.
Summary Background The relationships of thrombin generation (TG) with cardiovascular disease risk are underevaluated in population‐based cohorts. Objectives To evaluate the relationships of TG influenced by the contact and tissue factor coagulation pathways ex vivo with common single‐nucleotide polymorphisms (SNPs) and incident cardiovascular disease and stroke. Patients/Methods We measured peak TG (pTG) in baseline plasma samples of Cardiovascular Health Study participants (n = 5411), both with and without inhibitory anti‐factor XIa antibody (pTG/FXIa−). We evaluated their associations with 50 000 SNPs by using the IBCv2 genotyping array, and with incident cardiovascular disease and stroke events over a median follow‐up of 13.2 years. Results The minor allele for an SNP in the FXII gene (F12), rs1801020, was associated with lower pTG in European‐Americans (β = − 34.2 ± 3.5 nm; P = 3.3 × 10−22; minor allele frequency [MAF] = 0.23) and African‐Americans (β = − 31.1 ± 7.9 nm; P = 9.0 × 10−5; MAF = 0.42). Lower FXIa‐independent pTG (pTG/FXIa–) was associated with the F12 rs1801020 minor allele, and higher pTG/FXIa– was associated with the ABO SNP rs657152 minor allele (β = 16.3 nm; P = 4.3 × 10−9; MAF = 0.37). The risk factor‐adjusted ischemic stroke hazard ratios were 1.09 (95% confidence interval CI 1.01–1.17; P = 0.03) for pTG, 1.06 (95% CI 0.98–1.15; P = 0.17) for pTG/FXIa–, and 1.11 (95% CI 1.02–1.21; P = 0.02) for FXIa‐dependent pTG (pTG/FXIa+), per one standard deviation increment (n = 834 ischemic strokes). In a multicohort candidate gene analysis, rs1801020 was not associated with incident ischemic stroke (β = − 0.02; standard error = 0.08; P = 0.81). Conclusions These results support the importance of contact activation pathway‐dependent TG as a risk factor for ischemic stroke, and indicate the importance of F12 SNPs for TG ex vivo and in vivo.